Novotel Cikini Resilience as One of The Hotel Businesses in Jakarta - Simorangkir, Claudia Simponi Nehemia; Nugraha, Rizki Nurul (West Science Business and Management, 2024)
Novotel Cikini is a four-star hotel located in South Jakarta. During the Covid- 19 pandemic, Novotel was one of the hotels affected by covid. Therefore, Novotel must strive to maintain its business in the covid era with a special strategy. The strategy itself is a plan that is prepared with the aim of achieving something that has been determined. One of the existing strategies is marketing strategy. Marketing strategies are usually used by corporate companies with the aim of one of which is to survive in Covid-19. The method used in this research is a research method with a qualitative approach, the analysis method used is the SWOT analysis method. The results of this study indicate that Novotel had a strategy before Covid-19 in the form of implementing targeting, positioning, segmenting strategies. While the strategy during the pandemic is to use a pivoting strategy, positioning strategy, contact experience. For strategies after covid are short-term, medium-term, and long-term strategies.